Analysis of the Impact of Urban Microclimate on Air Conditioning Load Control - Hu, Xiaoqing; Wang, Beibei; Ji, Wenlu; Shen, Peifeng; Chen, Peng (MATEC web of conferences, 2016)
Due to the presence of urban heat island effect (UHIE), high humidity and other urban microclimate, temperature of city central area rises. This causes that the actual air-conditioning energy consumption (ACEC) in the urban central area is much higher than that in the suburbs. Load control of air-conditioners (ACs) is considered to be equivalent to a power plant of the same capacity, and it can greatly reduce the system pressure to peak load shift. In this paper, a simplified second order transfer function control model of ACs is presented, and its parameters will be influenced by the ambient temperature and urban microclimate. The temperature is obtained by using the temperature inversion algorithm of the heat island effect. Then, the heat index is calculated by combining temperature and humidity. The ambient temperature index of urban central area is modified based on the above microclimate, and the second order linear time invariant model of aggregated ACs is upgraded to the linear time varying model. Furthermore, the consequent parameter changes of the second order transfer function model are studied and the influence of urban microclimate on AC load control is analyzed. The proposed method is verified on numerical examples